In-season and off-season variation in physical fitness parameters of elite young soccer players - Bidaurrazaga-Letona, I.; Lekue, J. A.; Gil, S. M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The assessment of physical fitness changes at various moments during the development of youth soccer players is of relevance to measure the effectiveness of training. As such, the aim of the present study was to describe the changes in physical fitness of elite young soccer players exposed to systematic training. Methods: The present study involved a mixed cross-sectional and longitudinal analysis of the development of young soccer players of a professional soccer academy during three competitive seasons. The players started being part of the Under-12 (U12, n=55) category and, subsequently, they passed through the Under-13 (U13, n=39) and Under-14 (U14, n=27) categories. Players were evaluated annually at the beginning (September) and at the end (June) of the competitive season. The following variables were measured: 15 m velocity test, Yo-Yo intermittent recovery test (Level 1) (Yo-Yo IR1) and counter-movement jump (CMJ). A pairwise analysis was employed to establish the percentage change in the variables between consecutive sessions. A one way ANOVA was used to determine if there were any significant differences in the magnitude of the change across different ages. Only players with results for consecutive test sessions were included in each pairwise analysis. Results: As age increased significant improvements were observed in all the performance tests (p< 0.001). Besides, a pronounced improvement was observed in all the tests during the U14 season (10.2 %, 51.0 % and 8.1 % for velocity, Yo-Yo IR1 and CMJ, respectively). In contrast, during the off-season between U13 and U14 categories decrements in Yo-Yo IR1 (-1.7%, p< 0.01) and velocity (-4.1%, p< 0.001) were found. Discussion: The present results showed performance spurts in speed, endurance and jump that may occur at different moments depending on the maturation tempo and timing of the players. Indeed, previous research has shown that these improvements may be a contribution of the growth spurt related to the increases in body dimensions and muscle mass (Malina et al., 2004). However, an evident decrement in performance was observed in all the tests in the U13 off-season indicating a possible effect of detraining at this age. Altogether, this information can improve insight into the development of a specific group and can assist in an appropriate talent development program design.